“Costo por procesos de producción del plátano hartón (musa paradisiaca) de la finca Rumiquincha del cantón La Maná, provincia de Cotopaxi, año 2020” - Molina Gavidia, Erika Guadalupe (2021)
The general objective of this research project is to determine the costs by production process of “hartón” plantain of the “RUMICHINCHA” farm, Canton La Maná, province of Cotopaxi, which was born with the research problem of not having a model to determine the costs of production on the farm, making it difficult to obtain information in marking investment decisions to improve production processes, for which the inductive, deductive and analytical-synthetic methods were applied, which allowed the development of techniques; The interview which identified the production process of “hartón” plantain and the survey where it was deduced that employees have different obligations, identifying the following shortcomings: The producers do not have a good control of their costs incurred in each activity developed, so the unit cost of planting per hectare for the year was determined with a value of $742.58, in production the unit value per bunch was $1.10 and in the harvesting process the cost per box for the year was established with a value of $2.77, which are calculated for five hectares of plantain. Through the research carried out, it is suggested that Rumiquincha Farm apply the cost system model by production processes, in order to make the right decisions when determining the unit cost in each process and the profit for the farm.